Sosialisasi Penguatan Kewirausahaan yang Kreatif dan Inovatif Bagi Masyarakat Negeri Rutong - Audry Leiwakabessy; Ludwina Pormes; Gloria Sapulette; Joy Gaspersz; Goziana Armagita; Ronald D. Hukubun; Angela Ruban (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Socialization of strengthening creative and innovative entrepreneurship is carried out with the target of Rutong Village MSME actors. This socialization led MSME actors to be able to broaden their knowledge and increase their skills in running a business. There are problems faced such as human resources, limited administrative capacity, limited speculative capital and working capital, ability to grow and enter the market. This socialization was also carried out to answer and provide solutions that were faced by MSME in Rutong Village.